First mirror test in JET for ITER: Complete overview after three ILW campaigns. (May 2019) - Moon, Sunwoo; Petersson, P.; Rubel, M.; Fortuna-Zalesna, E.; Widdowson, A.; Jachmich, S.; Litnovsky, A.; Alves, E.; ,
Highlights: Test mirrors exposed in JET during a single ILW-3 campaign and all three campaigns, ILW1-3, were studied with optical, spectroscopy and microscopy methods. Total reflectivity has been maintained by mirrors from the main chamber wall, but all divertor mirrors lost optical performance. Divertor mirrors are coated with beryllium-rich layers (90–900 nm) containing admixtures of D, C, N, O, Ni and W. Accumulation of dust particles such as metal splashes (Be, Ni, Fe, W), fragments of be co-deposits occurred on divertor mirrors. Abstract: The First Mirror Test for ITER has been carried out in JET with mirrors exposed during: (i) the third ILW campaign (ILW-3, 2015–2016, 23.33 h plasma) and (ii) all three campaigns, i.e. ILW-1 to ILW-3: 2011–2016, 63, 52 h in total. All mirrors from main chamber wall show no significant changes of the total reflectivity from the initial value and the diffuse reflectivity does not exceed 3% in the spectral range above 500 nm. The modified layer on surface has very small amount of impurities such as D, Be, C, N, O and Ni. All mirrors from the divertor (inner, outer, base under the bulk W tile) lost reflectivity by 20–80% due to the beryllium-rich deposition also containing D, C, N, O, Ni and W. In the inner divertor N reaches 5 × 10 17 cm −2, W is up to 4.3 × 10 17 cm −2, while the content of Ni is the greatest in the outer divertor: 3.8 × 10 17 cm −2 . Oxygen-18 used as the tracer in experiments at the end of ILW-3 has been detected at the level of 1.1 × 10 16 cm −2 . The thickness of deposited layer is in the range of 90 nm to 900 nm. The layer growth rate in the base (2.7 pm s − 1 ) and inner divertor is proportional to the exposure time when a single campaign and all three are compared. In a few cases, on mirrors located at the cassette mouth, flaking of deposits and erosion occurred.